Review of Schismatogobius (Gobiidae) from Japan, with the description of a new species - Maeda, Ken; Saeki, Toshifumi; Shinzato, Chuya; Koyanagi, Ryo; Satoh, Nori (Ichthyological research, 2018)
Three species of Schismatogobius de Beaufort 1912 , distinguished by their morphology and mitochondrial DNA sequences, were found in freshwater streams in the Ryukyu Archipelago, Japan. Although two species were previously known from Japan ( S. roxasi Herre 1936 and S. ampluvinculus Chen, Shao, and Fang 1995), the taxonomy needs to be revised. To identify these species, the holotype morphology of S. marmoratus (Peters 1868 ), S. bruynisi de Beaufort 1912 , and S. roxasi , originally described from the Philippines and Indonesia, were examined and re-described here, because relatively little information about their diagnostic characters was provided in the original descriptions. The three Japanese species were identified as S. ampluvinculus , S. marmoratus , and a new species. They were distinguished from each other and from their congeners by the banding pattern of the body, markings on the pectoral fins, pigment patterns on the ventral surface of the head and pelvic fin, body depth at the pelvic-fin origin, pre-anal length, and pectoral-fin ray counts. Although the new species had been regarded as S. roxasi in previous publications, we show that it is actually not S. roxasi and that it also differs from all other nominal species of Schismatogobius . This is described as a new species, S. ninja . Additionally, this is the first record of S. marmoratus from Japan.